2000
DOI: 10.1182/blood.v95.1.309.001k17_309_313
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of increased angiogenesis in patients with acute myeloid leukemia

Abstract: Angiogenesis plays a key role in solid tumor growth. The purpose of this work was to study angiogenesis in acute myeloid leukemia (AML). We stained bone marrow samples from 20 adult patients with untreated AML and 20 normal controls using endothelial cell markers (ULEX-E and von Willebrand factor [vWF]). The number of vessels per millimeter length of bone marrow core biopsy specimen was scored by light microscopy. Using ULEX-E staining, AML marrows had (average ± SEM) 8.3 ± 3.6 vessels/mm (range, 3.7-19.3), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In addition, a few studies have demonstrated that metabolic change and hypoxia could enhance exosome release from blasts and/or BMSCs, stabilize HIF‐1α and activate the CXCR4/SDF‐1 axis in AML cells and eventually chemoresistance (K. Chen et al, ; Ohyashiki, Umezu, & Ohyashiki, ). Also, it has been revealed that the phosphorylated‐STAT3 involved in upregulation of VEGF on AML cells (Hussong, Rodgers, & Shami, ). Kalinkovich et al () also indicated the MVs capability in transferring CXCR‐4 to AML‐derived HL‐60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have demonstrated that metabolic change and hypoxia could enhance exosome release from blasts and/or BMSCs, stabilize HIF‐1α and activate the CXCR4/SDF‐1 axis in AML cells and eventually chemoresistance (K. Chen et al, ; Ohyashiki, Umezu, & Ohyashiki, ). Also, it has been revealed that the phosphorylated‐STAT3 involved in upregulation of VEGF on AML cells (Hussong, Rodgers, & Shami, ). Kalinkovich et al () also indicated the MVs capability in transferring CXCR‐4 to AML‐derived HL‐60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow vascularization is altered in AML with an increased micro-vessel density consequence of the production of pro-angiogenic factors like vascular endothelial growth factor (VEGF) (96)(97)(98)(99). AML progression induces the production of nitric oxide (NO) which increases vascular permeability and maintains overall hypoxia (100).…”
Section: Remodeling Of the Hematopoietic Niche By Leukemic Cellsmentioning
confidence: 99%
“…Disruption of vascular endothelial integrity represents an important step in the progression of leukemia within the bone marrow. Primary human AML bone marrow biopsies display increased blood vessel formation when compared with healthy bone marrow (Hussong et al, 2000). This is supported by AML xenograft studies and preclinical B-cell ALL (B-ALL) studies, whereby leukemic bone marrow colonization induces bone marrow angiogenesis, a significant increase in nitric oxide production (e.g., NOS3), and increased vascular permeability and hypoxia (Benito et al, 2011;Passaro et al, 2017).…”
Section: Cellular Components Of the Leukemic Microenvironmentmentioning
confidence: 87%
“…Many studies use static bone marrow imaging to infer localization of cellular components, including studies of hematopoietic stem and progenitor cell localization (Acar et al, 2015;Bruns et al, 2014;Coutu et al, 2018;Pinho et al, 2018); however, leukemic cells are highly motile, and therefore live imaging approaches and spatial transcriptomic approaches (Baccin et al, 2019 Preprint) may highlight unappreciated niche dependencies. Hussong et al, 2000;Benito et al, 2011;Passaro et al, 2017 HIF induction associated with B-ALL and AML chemo-resistance Muz et al, 2014;Wellmann et al, 2004 The CXCR4/CXCL12 axis and adhesive interactions through CD44 promote leukemic cell survival Schneider et al, 2002;Spoo et al, 2007;Passaro et al, 2015;Pitt et al, 2015;Sison and Brown, 2011;Fedorchenko et al, 2013;Godavarthy et al, 2019;Jin et al, 2006;Krause et al, 2006 MSCs MSCs Support IKZF1-mutant B-ALL relapse and may promote chemoresistance, but not in T-ALL Churchman et al, 2015;Joshi et al, 2014;Vitanza et al, 2014;Duan et al, 2014;Hawkins et al, 2016;Gomariz et al, 2018; AML cells induce osteogenic differentiation Battula et al, 2017 Associate with SNS to regulate HSC mobilization and regeneration following chemotherapy Ho et al, 2019;Katayama et al, 2006;Lucas et al, 2013;Maryanovich et al, 2018;Méndez-Ferrer et al, 2010;…”
Section: Cellular Components Of the Leukemic Microenvironmentmentioning
confidence: 99%